PERFORMANCE ANALYSIS OF TRAFFIC FLOW USING GREENSHIELDS, GREENBERGH, AND UNDERWOOD METHODS ON AHMAD YANI KM 40 MARTAPURA ROAD - Cathleen Ariela T S; Rosehan Anwar (Universitas Lambung Mangkurat, 2017)
Jl. Ahmad Yani km 40 investigated in order to determine the the level of service of the roads , as well as predictions made in order to determine the level of service of roads in the future.Three models of traffic through the model approach Greenshields, Greenberg and Underwood selected to serve as guidelines to get the Level of service on a road section. The model equations for the flow Banjarbaru- Martapurais Greenshield , maximum volume amounted to 2480.8 smp / clock speed and the amount of 25.64 km / hour and the density of 96.75 smp / km, while for the current Banjarbaru Martapura- obtained with models Underwood, the maximum volume amounted to 2634.4 smp / clock with massive speed of 26 344 km / hour and a density of 100 smp / Km.Based on these two models, the level of service of Banjarbaru-Martapura is C and Martapura- Banjarbaru is C. Then calculated the condition of the existing level of service is F (DS> 1.00). Once that is done traffic diversion for all heavy vehicles and light vehicles partly as an alternative treatment. Administering these alternatives, the index level of service changed to C (DS <0.8).Keywords :Greenshield methods, Greenberg methods, Underwood methods, Prediction, and Solutions.